2019
DOI: 10.1021/acs.est.9b02868
|View full text |Cite
|
Sign up to set email alerts
|

La2O3 Nanoparticles: Study of Uptake and Distribution in Pfaffia glomerata (Spreng.) Pedersen by LA-ICP-MS and μ-XRF

Abstract: The production and use of nanoparticles (NPs) in different fields increased in the last years. However, some NPs have toxicological properties, making these materials potential emerging pollutants. Therefore, it is important to investigate the uptake, transformation, translocation, and deposition of NPs in plants. In this work, laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) and micro X-ray fluorescence (μ-XRF) were used to investigate the uptake and translocation of La2O3 NPs to stem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…A comparison between the fold changes in P content with reference to untreated control as determined by XRF and analytical techniques is shown in ESI Figure 5 . Similarly, by using XRF, some previous studies have reported the increased Ti concentrations in cucumbers after exposure to TiO 2 NMs [ 70 ], increased Ce and Zn in corn exposed to CeO 2 and ZnO NMs [ 71 ], increased La levels in stems and leaves of Pfaffia glomerate (Spreng) after exposure to La 2 O 3 NMs [ 72 ] and increased Si and P in Deschampsia caespitosa (L.) Beauv. following exposure to Si and P NMs [ 44 ].…”
Section: Resultsmentioning
confidence: 97%
“…A comparison between the fold changes in P content with reference to untreated control as determined by XRF and analytical techniques is shown in ESI Figure 5 . Similarly, by using XRF, some previous studies have reported the increased Ti concentrations in cucumbers after exposure to TiO 2 NMs [ 70 ], increased Ce and Zn in corn exposed to CeO 2 and ZnO NMs [ 71 ], increased La levels in stems and leaves of Pfaffia glomerate (Spreng) after exposure to La 2 O 3 NMs [ 72 ] and increased Si and P in Deschampsia caespitosa (L.) Beauv. following exposure to Si and P NMs [ 44 ].…”
Section: Resultsmentioning
confidence: 97%
“…The energy spectra for different elements analyzed in rice plants after 30 days of treatment with nHAP and nP along with the control untreated plants are shown in Figure C. Previously, this technique has been employed to monitor the uptake of P in sugarcane, titania NMs in cucumber, ceria and zinc oxide NMs in corn, and lanthanum oxide (La 2 O 3 ) NMs in the stem and leaves of Pfaffia glomerata (Spreng) . Silicon and P in plants have also been determined using XRF previously in Deschampsia caespitosa (L.) Beauv …”
Section: Resultsmentioning
confidence: 99%
“…For instance, a spatial resolution down to 50 nm was reported for the latest synchrotron-based nano-XRF . Elemental mapping by μ-XRF has been used, alone or in combination with mass spectrometry-based imaging techniques (to be discussed later), to characterize the distribution of nanomaterials in plant , and animal tissues. , Note that EDS and EELS are static techniques generating elemental information on samples fixed on sample holders, whereas in situ XRF analysis with high temporal resolution can provide dynamic information on nanomaterial properties. In fact, spatially resolved XRF microscopy with sub-100 nm spatial resolution was recently applied to acquire quasi-real-time elemental maps of ZnO nanorods in simulated wastewater .…”
Section: Methods To Identify Characterize and Quantify Nanomaterials ...mentioning
confidence: 99%